Gaya Hidup Hijau: Membeli E-Ticket - Christina Rahardja Honantha (Conference In Business, Accounting, And Management (CBAM), 2012)
Be green in style is popular today. There are several activities of â€œgreen chicâ€; eco fashions, go online shopping, and buy local. Purpose of this study was to describe consumer behavior in Surabaya consuming e-ticketing services in business aviation low cost carrier (LCC) as one of green in style. Using the elements of consumer behavior study; 5W 1H. In this research, respondents are who had bought and used e-ticketing services in business aviation low cost carrier (LCC) in Surabaya at least 2 times in the last 1 year, buying and using the services of low cost carrier airlines (LCC) with buy e-ticketing service for personal gain, based in Surabaya, graduate a minimum high school education. Analysis use frequency tables, tables percentage bar charts and cross tabulations method. This research result showed that e-ticketing service users in the business aviation low cost carrier (LCC) most were women. Respondents use e-ticketing service for holidays. The reason uses e-ticketing services because of practical. Respondents usually frequent purchases and travel by purchasing tickets using e-ticketing service between 2-4 times in the last 1 year. At the end, majority of respondents were satisfied after using e-ticketing service due to time saving and practical.Keywords: Green marketing, green lifestyle, consumer behavior, online shopping for e-ticketing.